Comparative Efficiency of Lutein and Astaxanthin in the Protection of Human Corneal Epithelial Cells In Vitro from Blue-Violet Light Photo-Oxidative Damage - Martina Cristaldi; Carmelina Daniela Anfuso; Giorgia Spampinato; Dario Rusciano; Gabriella Lupo (Applied Sciences, 2022)
The aim of this study was to compare in vitro the protective and antioxidant properties of lutein and astaxanthin on human primary corneal epithelial cells (HCE-F). To this purpose, HCE-F cells were irradiated with a blue-violet light lamp (415–420 nm) at different energies (20 to 80 J/cm2). Lutein and astaxanthin (50 to 250 μM) were added to HCE-F right before blue-violet light irradiation at 50 J/cm2. Viability was evaluated by the CKK-8 assay while the production of reactive oxygen species (ROS) by the H2DCF-DA assay. Results have shown that the viability of HCE-F cells decreased at light energies from 20 J/cm2 to 80 J/cm2, while ROS production increased at 50 and 80 J/cm2. The presence of lutein or astaxanthin protected the cells from phototoxicity, with lutein slightly more efficient than astaxanthin also on the blunting of ROS, prevention of apoptotic cell death and modulation of the Nrf-2 pathway. The association of lutein and astaxanthin did not give a significant advantage over the use of lutein alone. Taken together, these results suggest that the association of lutein and astaxanthin might be useful to protect cells of the ocular surface from short (lutein) and longer (astaxanthin) wavelengths, as these are the most damaging radiations hitting the eye from many different LED screens and solar light.